The influence of personal, social and institutional factors on tax compliance behaviour of Malaysian individual taxpayers / Loo Ern Chen and Afidah Sapari - Ern Chen, Loo; Sapari, Afidah (2010)
Tax enforcement and deterrence strategies such as penalty, tax audit, tax investigation and forensic accounting have been practiced by the Inland Revenue Board (IRB) in increasing tax compliance and reducing tax evasion (IRB Annual Report, 2004, 2005). Besides these, it is important for the policy makers to understand other sociological and psychological factors (other than economics) that may affect tax compliance behaviour of the individual taxpayers. Therefore, the main objective of this study is to investigate the sociological and psychological factors that may affect tax compliance behaviour of the Malaysian individual taxpayers especially under the Self-Assessment (SA) system. The variables selected are mainly derived from a theoretical model based on the Ajzen’s (1991) Theory of Planned Behaviour(TPB) but will be expended to be more rigorous in explaining the taxpayers ‘compliance behaviour. The objective of this study can be achieved depending on the motivational strength the tax system instils in taxpayers to do the tax filing, submit the tax returns on time, reporting the correct amount subject to tax and paying the correct amount of tax due. On the surface, SA system may appear to be able to enhance compliance(IRB Annual Report 2004, 2005). However, tax compliance goes further than the need to comply with the law. It involves the need to change the mind-sets, attitudes and obligations of individual taxpayers. How Malaysian taxpayers react with this statutory obligation? The question of whether the taxpayer is aware of the consequences of the SA system and voluntary comply by filing complete tax returns, reporting a correct amount of income subject to tax and paying the correct amount of tax to the IRB can be answered by analysing their behaviour in filing, reporting and paying income tax liability. This study then has to investigate the factors that may affect tax compliance behaviour of Malaysian individual taxpayers in compiling their tax returns and whether the government achieves the objective of enhancing tax compliance. Since tax compliance were proved to be affected by the changes in tax structure (such as tax law, tax rate, fines and tax audit) (e.g., Wigel, Hessing & Elffers, 1987; Plumly,1996; Trivedi, Shehata & Lynn, 2003) it is very important for the IRB to identify and understand other non-economic factors in enhancing tax compliance. Designing effective policies in enhancing tax compliance not only focusing on economic and deterrence factors. It requires understanding the behavioural aspects of the tax compliance decision of the taxpayers. Individual behaviour towards tax compliance is a function of personal, social and institutional factors and enhancing these factors are desirable policy instruments to complement the usual enforcement options. The effect of ethics and moral value, perceived behavioural control and subjective norms on tax compliance behaviour are not well understood and investigating this gap is the focus of this study. The survey method is the main research design for this study. It provides a good source of information and feedback about social and psychological behaviour of taxpayers. This method is used to identify a specific sociological and psychological theory on how individuals make decisions and whether it applies to tax compliance. The main advantage is that this method includes many socio-economic, demographic and attitudinal variables (Sekaran, 2007; Parmjit, Chan & Sidhu, 2008). Therefore survey is the most appropriate method in this study since it can compare different demographic and socio-economic variables of the taxpayers and get insight into taxpayer’s moral value, attitudes, perceived behavioural control, social norms and perceptions on the fairness of the tax system.